Development and Validation of a Stability-Indicating HPLC Method for the Simultaneous Determination of Florfenicol and Flunixin Meglumine Combination in an Injectable Solution - Nidal Batrawi; Hani Naseef; Fuad Al-Rimawi (Journal of Analytical Methods in Chemistry)
The combination of the powerful antimicrobial agent florfenicol and the nonsteroidal anti-inflammatory flunixin meglumine is used for the treatment of bovine respiratory disease (BRD) and control of BRD-associated pyrexia, in beef and nonlactating dairy cattle. This study describes the development and validation of an HPLC-UV method for the simultaneous determination of florfenicol and flunixin, in an injectable preparation with a mixture of excipients. The proposed RP-HPLC method was developed by a reversed phase- (RP-) C18e (250 mm × 4.6 mm, 5 μm) column at room temperature, with an isocratic mobile phase of acetonitrile and water mixture, and pH was adjusted to 2.8 using diluted phosphoric acid, a flow rate of 1.0 mL/min, and ultraviolet detection at 268 nm. The stability-indicating method was developed by exposing the drugs to stress conditions of acid and base hydrolysis, oxidation, photodegradation, and thermal degradation; the obtained degraded products were successfully separated from the APIs. This method was validated in accordance with FDA and ICH guidelines and showed excellent linearity, accuracy, precision, specificity, robustness, LOD, LOQ, and system suitability results within the acceptance criteria.